Integrasi Nilai â€œSi Tou Timou Tumou Touâ€ Dengan Etika Penggunaan Ai Dalam Pendidikan Tinggi Sulawesi Utara - Galang Christ Fransisco Misa (Journal of Tourism Sciences, Technology and Industry, 2025)
This paper explores the integration of the Minahasan cultural value â€œSi Tou Timou Tumou Touâ€â€”the principle of educating and humanizing othersâ€”with the ethical use of Artificial Intelligence (AI) in higher education in North Sulawesi. As AI becomes increasingly present in teaching, learning, and research activities, it is essential to ensure that its application supports, rather than diminishes, the human role in education. The value â€œSi Tou Timou Tumou Touâ€ provides a human-centered foundation that guides AI use toward enhancing studentsâ€™ intellectual and moral development. Key ethical concerns include academic integrity, transparency, responsible data use, fairness, and avoiding excessive dependence on AI-generated outputs. Integrating local wisdom encourages universities to adopt AI in ways that strengthen collaboration, creativity, and social responsibility. This study concludes that blending cultural values with modern AI ethics can create an educational environment that remains technologically advanced while upholding humanity, character formation, and cultural identity.Â